The Influence of Organizational Culture, Job Satisfaction and Work Motivation on Employee Performance (Study on Shop X Bandung City Branch) - Cindy Calista; Wilson Bangun (Syntax Idea)
Optimal employee's perfomance support their organization goals. In this research, it is found that the employee's attendance levels are not yet implemented optimally. The aim of this research is to determine the influence of the organization culture, job satisfaction and work motivation on the employee's performance. The population of Shop X employees in the Bandung city branch is 551 employees, a sample of 232 employees. The research method is using quantitative approach using SPSS 25. The research result shows that the organization culture, job satisfaction and work motivation has significant impact towards the employee's performance. Altogether, organization culture, job satisfaction and work motivation are important factors in improving the employee's performance.